2011
DOI: 10.1002/art.30212
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in type I hemidesmosome components suggestive of epigenetic control in the salivary glands of patients with Sjögren's syndrome

Abstract: Objective. Acinar cells in the salivary glands of patients with Sjögren's syndrome (SS) display severe alterations in anchorage to the basal lamina. Bioinformatics analysis of the BP230 gene sequence has revealed the presence of CpG islands that might be involved in epigenetic control of gene expression, and methylation of the BP230 promotor region may be implicated as an epigenetic control mechanism in salivary gland damage. Thus, the present study was undertaken to evaluate the protein BP230, as well as prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 49 publications
(64 reference statements)
0
21
0
Order By: Relevance
“…We found that expression of total TLR2 was significantly increased in intestinal mucosa from UC patients in comparison to CD and controls, although the expression of TLR2 mRNA was not significantly different among groups. While this finding may appear contradictory, similar observations were reported in Sjögren Syndrome for BP230 protein levels (Gonzalez et al 2011). According to these studies, in Saccharomyces, a difference between relative transcription and translation efficiency has been documented (Tuller et al 2007), suggesting that the cell preserves a global equilibrium between the processes.…”
Section: Discussionmentioning
confidence: 60%
“…We found that expression of total TLR2 was significantly increased in intestinal mucosa from UC patients in comparison to CD and controls, although the expression of TLR2 mRNA was not significantly different among groups. While this finding may appear contradictory, similar observations were reported in Sjögren Syndrome for BP230 protein levels (Gonzalez et al 2011). According to these studies, in Saccharomyces, a difference between relative transcription and translation efficiency has been documented (Tuller et al 2007), suggesting that the cell preserves a global equilibrium between the processes.…”
Section: Discussionmentioning
confidence: 60%
“…LSGs were obtained as previously described [17]. Following surgery, samples were split into two portions.…”
Section: Biopsiesmentioning
confidence: 99%
“…An MMP/TIMP expression ratio greater than 1 was taken to indicate that degradative activity was increased. For laminin and collagen IV changes in immuno staining intensity were apparent in the basal lamina and ducts of acini, while no such changes were detected in capillaries situated in close proximity of these structures [104,105]. These observations indicated that salivary glands from SS-patients produced enzymes that destroyed their own basal lamina, which did not diffuse through the ECM.…”
Section: Altered Organization Of the Apical Pole Of Salivary Acinar Cmentioning
confidence: 85%
“…This integrin is crucial to the organization of adhesion complexes called hemidesmosomes, which are responsible for cell anchorage to the basal lamina. Changes in a6b4 integrin and other components of this basal adhesion complex detected in SS-patients have been reviewed extensively elsewhere [105,107].…”
Section: Altered Organization Of the Apical Pole Of Salivary Acinar Cmentioning
confidence: 99%